Towards a state-of-the-art of the current researches on disinformation / misinformation - Romero Rodríguez, Luis (2013)
The concepts of disinformation and misinformation have almost as many meanings as the number of authors who have treated them. Considered from the semiotic and psychological point of view, disinformation and misinformation seem to be the result of the inadequacy of what is communicated to the reality of an object. The focus of both Political Science and Public Relations is set on disinformation / misinformation as an example of how masses and public opinion can be manipulated, while the vision of Communication Sciences and Information considers such behaviours as natural features of the media in a clearly oversaturated communications ecosystem. This paper describes the different approaches to the topic of disinformation/misinformation made in the above mentioned scientific disciplines.